Kajian Kualitas Air dan Indeks Pencemaran Di Perairan Kampung Sejahtera Pulau Baai Kota Bengkulu - Yulisah Dwi Putri; Elfi Yuliza; Lizalidiawati Lizalidiawati (UNIB Press, 2021)
Water quality is one of the important factors supporting the growth of mangrove ecosystems. The activites of Kampung Sejahtera’s people were allegedly polluted the waters and disturbing the mangrove ecosystem. This study aimed to identify the status of water quality and pollution index in the waters of Kampung Sejahtera, Bengkulu City. The method used is a direct measurement at the research location which was carried out at 9 location points, 5 points representing the waters near the settlements of the prosperous village residents, and 4 location points representing the waters near the mangrove ecosystem. Then the results are compared with the Decree of the State Minister of the Environment No. 51 of 2004 concerning seawater quality standards for marine biota and to determine the status of water quality by using the pollution index method based on the Decree of the State Minister of the Environment No. 115 of 2003. The results of this study indicate that the temperature parameter, salinity, and pH met the quality standard while the TSS and DO parameters did not fulfill the quality standard. Based on the results of the calculation of the pollution index that the waters of Kampung Sejahtera are in the category of good condition to lightly pollute.